How did mammals evolve into their ecological niches through time? Quantitative tests for classic macroevolutionary questions - Benevento, G (2018)
Observations that the taxonomic and ecomorphological diversity of mammals increased across the Cretaceous/Paleocene (K/Pg) boundary led to the model of adaptive radiation. These rapid and large-scale increases in diversity and disparity are thought to have resulted from unprecedented ecological opportunity for mammals in the wake of the K/Pg event, during which numerous niches previously occupied by the non-avian dinosaurs and other components of the Mesozoic fauna were cleared. Although patterns of increased body size and body size disparity have been thoroughly explored, fundamental questions remain regarding both the magnitude and exact nature of mammalian ecomorphological change across the K/Pg boundary. It has long been established that Cenozoic mammals appear to exhibit a wider range of ecomorphotypes associated with feeding ecology in comparison to the Mesozoic. Here I use a dataset of six functionally-relevant traits made up of ten continuous character measurements across 276 fossil and 730 modern (including 23 recently extinct Pleistocene megafauna) mammal jaws to quantify and explore patterns of jaw ecomorphological disparity from the Late Triassic– end-Eocene and Pleistocene–Recent. I further explore the evolutionary rate across the K/Pg boundary by analysing six functional jaw traits for 69 Jurassic- Eocene mammals in a phylogenetic framework. The results presented herein demonstrate that, despite an immediate increase in therian mammal jaw ecomorphological disparity across the K/Pg boundary, mammals as a whole did not show an increase until the Paleocene/Eocene boundary. This lag of ~10 My is interpreted as an interval of ecological recovery, during which high rates of mandibular ecomorphological trait evolution are detected. Much of the Paleocene/Eocene increase in disparity can be attributed to mammals with larger body sizes. My results are indicative of an adaptive radiation of placental mammals in the early Paleogene, in response to large-scale niche clearing.